KAJIAN LOKASI TERCEMAR LEPTOSPIRA Sp PADA KASUS FOKUS DI RW 02 KELURAHAN BANDARHARJO KOTA SEMARANG TAHUN 2019 - Reyininda Agustyafi Martyarini; Suharyo - -; Mada Gautama; Wiwik Dwi Lestari (Dian Nuswantoro Semarang, 2020)
Data in RW 02 Bandarharjo Semarang regency shows that every year since 2017-2019 there are always deaths due to leptospirosis. The purpose of this study is to mapping of leptospirosis and the mount of Rattus sp infected with Leptospira sp, describe the environmental conditions and hygiene behavior. A cross sectional method was used in this study. The study population included Rattus sp. and all houses in RW 02 Bandarharjo. Rattus sp. samples were all captured at the study site, while home samples totaled 48 houses around the house of leptospirosis patients within a radius of 150 meters. Data collection is done through environmental observations, interviews, collecting coordinate points, trapping, and laboratory tests. Examination of rat kidney blood samples was done by gram negative staining. A total of 13 rats were caught Rattus sp, 15.4% of them were indicated to be strongly positive containing Leptospira sp. All conditions of landfills are in an open condition, 89.6% of them are in front of the house, 45.8% of sewers are flooded with water that does not flow. There are 20.8% of respondents do not have the habit of washing hands / feet with soap, more than 50% of respondents ignore the use of protective equipment when cleaning sewers, warehouses, and rat droppings. There are 2 Rattus sp which are indicated to be strongly positive containing Leptospira sp. so that the mobility of Rattus sp can spread leptospirosis at the location in the buffer region.Keywords: leptospirosis, mapping, environment, health behaviour